Automated discovery and proof of congruence theorems for partial sums of combinatorial sequences. Issue 6 (2nd June 2016) - Chen, William Y. C.; Hou, Qing-Hu; Zeilberger, Doron
Abstract : Many combinatorial sequences (e.g. the Catalan and the Motzkin numbers) may be expressed as the constant term ofP ( x ) k Q ( x ), for some Laurent polynomials P ( x ) and Q ( x ) in the variable x with integer coefficients. Denoting such a sequence bya k, we obtain a general formula that determines the congruence class, modulo p, of the indefinite sum∑ k = 0 r p - 1 a k, for any prime p, and any positive integer r, as a linear combination of sequences that satisfy linear recurrence (alias difference) equations with constant coefficients. This enables us (or rather, our computers) to automatically discover and prove congruence theorems for such partial sums. Moreover, we show that in many cases, the set of the residues is finite, regardless of the prime p .